Building Open Pedagogy in Community Colleges - Gilpin, Staci Ann; Rollag Yoon, Stephanie; Lazzara, Julie (Online Learning, 2023)
This qualitative study examines open pedagogy as a critical instructional strategy in online community college settings to increase opportunities for authentic interactions that support student persistence. Discourse analysis was used to understand how community college students (n=78) perceive and connect with different aspects of open pedagogy activities. The study’s findings underscore the students’ awareness of their audience in online settings, their value of collaborative efforts to design digital materials, and the significance of acknowledging the digital learning context. Despite many students choosing to share their work publicly, challenges related to sharing work publicly were illuminated across reflective questionnaire responses. To address these issues, the study recommends enhancing media literacy, providing group collaboration options, and emphasizing institutional support. Further research should explore the influence of social media experiences and AI tools on the public sharing of open pedagogy activities. Ultimately, by embracing open pedagogy in online learning contexts while considering individual student identities and perceptions, community college settings can enhance online interactions, engagement, and student persistence.